Institutional Capacity of Forest Management Unit in Promoting Sustainable Community-Based Forest Management. Case Study of Forest Management Unit in Central Sulawesi Province, Indonesia - Sudirman Daeng Massiri; Adam Malik; Golar; Hamzari; Bramasto Nugroho (Institut Pertanian Bogor (IPB University), 2020)
The main issue of forest management policies in Indonesia is strengthening the role of Forest Management Unit (FMU) and community-based forest management. This study describes the performance of FMU and the priority needs for the institutional strengthening of FMU to promote community-based forest management in Central Sulawesi Province. The research applied a case study's descriptive method by exploring, classifying, and understanding the meaning of the problems encountered by the object examined. The study shows that the performance of the FMUs was not yet optimal in promoting community-based forest management. This problem attributed to the weak institutional capacity of FMU. Several aspects of the institution need improvements, including strengthening its capacity at the resort level, fulfilling the needs and capacity building of extension staff, as well as providing a legal mechanism for financial management to facilitate its business activities and cooperation. These priority needs were affected by government bureaucratic issues. It necessary the policy formulation governing the strengthening of community-based forest management in the FMU area that supports the independence goals of FMU.